Perancangan Penerangan Buatan Dengan Aspek Penghematan Energi Listrik Di Yayasan Putri Tujuh - Linwan Abadi Harefa; Feranita Feranita; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The intensity of illumination in a room should be in accordance with the need of that room, like the set standards of the Indonesia National Number 6197 in 2011. The study is intended to evaluate the system of lighting in the rooms and take into account the aspect of saving energy of the Yayasan Putri Tujuh Ujung Batu. From the result of the measurement directly by using Light Meter measurement tool obtained that strong lighting in the room do not meet the Indonesia National Standard. This research is carried out the intensity measurement of strong lighting in the Putri Tujuh Ujung Batu Foundation.. Cause of that, lamps evaluation of intensity by using of zonal cavity methods. Type of lamps suggested are five Philips LED with 33 Watts. The results of the calculation method are simulated using the DIALux Evo V.8.2 software which display on dimensional three image and intensity of illumination in the room. From simulation, the colour of wall with pure white increases the illumination intensity from 400 Luxes to be 556 Luxes. Saving Energy for SD Islam Inayah is 31,25 by using Philips LED compared to Hannochs lamps.Keywords: Zonal Cavity Method , Software DIALux Evo , Saving Energy.